NOVEL SUBCUTANEOUS SUSTAINED RELEASE NANOPARTICLES ENCAPSULATING LOW MOLECULAR WEIGHT HEPARIN (LMWH): PREPARATION, CHARACTERIZATION AND EVALUATION - Jogala, Satheesh; Chinnala, Krishna Mohan; Aukunuru, Jithan (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The objective of the current research work was to prepare and evaluate novel subcutaneous sustained release polymeric nanoparticles for low molecular weight heparin (LMWH). Methods: In this study, we prepared subcutaneously administered polymeric nanoparticles encapsulating LMWH using different grades of polycaprolactons (PCL) (14k, 45k, 80k) and 0.1% Polyvinyl alcohol (PVA) solution as surfactant by employing waterâ€“in-oil in-water (w/o/w) emulsion and evaporation method. The formulated nanoparticles were evaluated for size, shape, zeta potential, in vitro drug release, and in vivo biological activity (anti factor Xa activity) using standard kit, antithrombotic activity in thrombosis induced rat model. Drug and polymer interactions in the nanoparticles were evaluated using Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD). Results: Scanning electron microscopic (SEM) studies on the nanoparticles confirmed the formation of spherical particles with smooth surface. The size of the formed nanoparticles were about 415-495 nm. The % entrapment of nanoparticles was found to be between 69-81%. Nanoparticles showed slow and sustained pattern of release for about 59-65 % in 48 h. Optimized nanoparticles exhibited excellent improvement in pharmacokinetic parameters and showed good antithrombotic activity, Activated partial thromboplastin time (aPTT) activity when compared to free drug. FTIR studies indicated that there was no loss in chemical integrity of the drug upon fabrication into nanoparticles. XRD results demonstrated that the drug changed its physical form in the formulation. Conclusion: The results of this study revealed that subcutaneous nanoparticles were excellent candidates for sustained drug delivery of LMWH to avoid repeated subcutaneous administration. Keywords: Low molecular weight heparin, Subcutaneous, Stability, Polycaprolactone, Venous thrombosis, Activated partial thromboplastin time Â